2013
DOI: 10.1089/aid.2013.0025
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Drug Resistance in HIV-Infected Cambodian Children Who Are Undetected as Failing First-Line Antiretroviral Therapy by WHO 2010 Guidelines

Abstract: Antiretroviral therapy in resource-limited settings is monitored clinically and immunologically according to WHO guidelines. Frequent misclassification of virologic failure is reported, mostly in adults, leading to early therapy switch or late failure diagnosis. Pediatric treatment monitoring and resistance data upon first-line failure are limited, particularly when the 2010-WHO pediatric guidelines are used without routine viral load monitoring. We previously reported high treatment failure misclassification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…All naive patients harbored viruses that were resistant to NVP/EFV with a majority of them showing the K103N/S mutation. The rates of 181C/I, K103N/S G190A and M184L/V mutations were also higher than in another recent study in Cambodia among patients having a median duration of 12 months up to 4 years on antiretroviral therapy [6], [7], [30]. The level of transmitted drug resistance (TDR) in naive patients needs to be assessed and could explain the high level of resistance mutations for this population potentially more recently infected than pre-treated patients.…”
Section: Discussionmentioning
confidence: 82%
“…All naive patients harbored viruses that were resistant to NVP/EFV with a majority of them showing the K103N/S mutation. The rates of 181C/I, K103N/S G190A and M184L/V mutations were also higher than in another recent study in Cambodia among patients having a median duration of 12 months up to 4 years on antiretroviral therapy [6], [7], [30]. The level of transmitted drug resistance (TDR) in naive patients needs to be assessed and could explain the high level of resistance mutations for this population potentially more recently infected than pre-treated patients.…”
Section: Discussionmentioning
confidence: 82%
“…At that time, reports about children’s ART chiefly expressed concerns about the challenges of detecting treatment failures using only immunological and clinical criteria [ 16 ]. Later, with the development of HIV genotypic resistance testing, high resistance mutations were reported in children with virological failure on first-line ART [ 17 , 18 ]. However this testing was not yet routinely available.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the WHO 2010 pediatric guidelines, without routine viral load monitoring, treatment failure were misclassified for children on first-line therapy [ 16 , 17 ]. In addition, extensive drug resistance to first-line ART was described among 51 HIV-infected children, who were undetected as first-line ART failures under the WHO 2010 guidelines [ 18 ]. Similarly the HIV/Hepatitis laboratory of the Pasteur Institute in Cambodia reported the occurrence of mutations in children from routine samples collected between December 2004 and January 2011 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the reported sensitivity of clinical/immunological monitoring in detecting treatment failure is low, 29 %-33 % [ 36 ], many of these children will continue to be on failing first-line regimens. Several studies have shown that delayed detection of virological failure to first-line therapy often leads to development of drug resistance, jeopardizing potential second-line treatments [ 11 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%